Pemberdayaan Masyarakat dalam Kerajinan Sarung Tenun Lokal di Desa Ombarade, Kecamatan Wewewa Tengah, Kabupaten Sumba Barat Daya (Soetomo Administrasi Publik, 2025)
This research aims to analyze community empowerment in local woven sarong crafts in Ombarade Village, Southwest Sumba Regency. Woven sarong crafts are a cultural heritage that has high economic value and has the potential to become a leading sector in the creative economy. However, local craftsmen still face various obstacles such as limited market access, lack of product innovation, and minimal support in terms of technology and marketing. The research method used is descriptive qualitative with a case study approach. Data was collected through in-depth interviews, participant observation, and documentation of craftsmen, community leaders, and other related parties. The analysis was carried out based on community empowerment theory which includes the stages of awareness, capacity building and empowerment. The research results show that empowerment efforts have been carried out through various training programs, mentoring and marketing support. However, the effectiveness of this program is still limited due to the lack of policy continuity and the minimal active role of the government and the private sector. This study recommends innovation-based empowerment strategies, increasing the capacity of craftsmen, and collaboration with the private sector and government to expand market access and improve community welfare